Natural Products Biosynthesis by Streptomyces netropsis IMV Ac-5025 under Exogenous Sterol Action - Mariia Loboda; Liudmyla Biliavska; Galyna Iutynska; Jake Newitt; Ruslan Mariychuk (MDPI AG, 2024)
Streptomycetes are known as producers of bioactive substances, particularly antibiotics. Streptomyces netropsis IMV Ac-5025 simultaneously produces different classes of antibiotics, including polyene compounds, phytohormones, and sterols, but the metabolic pathways involved in their biosynthesis are largely understudied. The aim of this work was to explore the biosynthesis of polyene antibiotics, sterols, and phytohormones when the producer is cultivated in a nutrient medium supplemented with exogenous β-sitosterol. Gas chromatography and high-performance liquid chromatography were applied to analyze the spectrum of bioactive compounds. The obtained results demonstrated not only an increase in the accumulation of biomass but also polyene antibiotics, intracellular sterols, auxins, and cytokinins, when cultivating S. netropsis IMV Ac-5025 in a liquid medium with the addition of β-sitosterol. The amount of biomass raised 1.5-2-fold, whilst the sum of polyene antibiotics increased 4.5-fold, sterols' sum (ergosterol, cholesterol, stigmasterol, β-sitosterol, and 24-epibrassinolide) by 2.9-fold, auxins' sum (indole-3-acetic acid, indole-3-acetic acid hydrazide, indole-3-carbinol, indole-3-butyric acid, indole-3-carboxaldehyde, and indole-3-carboxylic acid) by 6-fold, and cytokinins' sum (zeatin, isopentyladenine, zeatin riboside, and isopentenyladenosine) by 11-fold. Thus, we put forward the hypothesis that β-sitosterol plays a regulatory role in the network of biosynthetic reactions of S. netropsis IMV Ac-5025.